Geometry of the décollement below eastern Bangladesh and implications for seismic hazard - Bürgi, Paula (2021)
Eastern Bangladesh sits on the seismically active Chittagong-Myanmar fold and thrust belt (CMFB), a north-trending accretionary wedge on the eastern side of the India-Eurasia collision. Earthquakes on the basal décollement and associated thrusts within the CMFB present a hazard to this densely populated region. In this study, we interpret 28 seismic reflection profiles from both published and unpublished sources to constrain the depth of the basal décollement. To convert profiles from the time domain to the depth domain, we integrate sonic log and seismic stacking velocity data to generate time-velocity relationships for different parts of the CMFB. Our analysis reveals that the décollement is ∼9 km deep in northeast and southeast Bangladesh, but shallows to ∼5 km in east-central Bangladesh. The décollement has an area of 7.25 × 104 km2 (∼150 × 450 km), making it capable of an Mw 8.5 earthquake. However, the warped geometry of this fault might act as a rupture barrier were a large earthquake to occur on the décollement. Our combined velocity and fault model lay the groundwork for future studies to address seismic segmentation, ground shaking, and rupture modeling in the CMFB. Finally, we use our compiled data set to analyze the evolution of fold kinematics in the CMFB. We observe that folding style and failure mode varies, from mainly ductile deformation in the foreland to mainly brittle in the hinterland. The dual-failure modes within the CMFB support the hypothesis that a region with ductile deformation may still be capable of seismic behavior.